Deployment of electronic multimedia technical documentation solutions: a longitudinal study in partnership with a defence contractor. (1st January 2013) - McArthur, D.; Lynn, J.S.; Thomson, R.
This paper details the research relationship and activity between the university and a commercial client working within the defence industry over a ten-year period. The investigative core deals with the contractor's requirement to address the paper to electronic conversion of technical documentation and maintenance procedures, and the financial requirements of reducing ongoing customer support cost, whilst providing a competitive advantage. From initial projects involving optical media/laptop computer multimedia applications, to the use and deployment of smart phone and PDA devices, and more recently the use of wearable computing systems/head mounted display/augmented reality assistance, the research study has tracked technological changes over the period, and the impact of the same on working practice. An additional factor common to many engineering industries is the capture and retention of acquired knowledge of an ageing workforce, directly connected to the cost of customer support.